Oscillation Results for First Order Nonlinear Neutral Dierence Equation with \Maxima" (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In this paper we consider the rst order nonlinear neutral dierenceequation with maxima of the form:and established some sucient conditions for the oscillation of all solutions of the above equation. Examples are provided to illus-trate the main results. 2010 AMS Subject